Risk of Neonatal Drug Withdrawal after Intrauterine Coexposure to Opioids and Psychotropic Medications: Cohort Study. Issue 2 (June 2018) - Huybrechts, K.F.; Bateman, B.T.; Desai, R.J.; Hernandez-Diaz, S.; Rough, K.; Mogun, H.; Kerzner, L.S.; Davis, J.M.; Stover, M.; Bartels, D.; Cottral, J.; Patorno, E
Abstract : ( BMJ . 2017;358:j3326) Neonatal abstinence syndrome is a recognized complication of intrauterine exposure to opioids. Neonatal abstinence syndrome can manifest in a number of different ways, from difficulty feeding and sleeping to more severe complications such as impaired thermoregulation, seizures, failure to thrive, and respiratory distress. Because pregnant women who are using an opioid often also use psychotropic medications, there are concerns about potential interactions between the opioid and psychotropic drugs leading to an increase in the occurrence and severity of neonatal drug withdrawal from. However, not much is known about how this risk varies by type of psychotropic medicine or about the risks associated with psychotropic polypharmacy. These investigators undertook the present study to determine whether the risk of neonatal drug withdrawal in newborns exposed in utero to one or more psychotropic medications in addition to opioids is greater and more severe than those exposed to opioids alone.